2010
DOI: 10.1891/1541-6577.24.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Health Practices: Cervical Cancer Screening Among Filipino Women

Abstract: This correlational study developed and tested theory to better understand health practices, including cervical cancer screening, among young Filipino women. It tested theoretical relationships postulated among (a) positive health practices, (b) cervical cancer screening, (c) social support, (d) acculturation, and (e) optimism. A convenience sample of 89 young Filipino women in an urban setting was obtained. Participants completed a demographic sheet and five instruments. Significant positive correlations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Sentell et al (2015) found low health literacy, as measured by self-reported understanding of print health-related materials, was significantly related to cervical screening. Lack of knowledge can be an important determinant of cervical screening (Ayres et al, 2010); however, basic knowledge of cervical screening was found in two studies (Holroyd et al, 2003;Yoo et al, 2011). In Holroyd et al's (2003) quantitative study in Hong Kong with 98 Filipino domestic workers, despite 53% reported never having participated in pap-testing, 78% of women had heard of pap-testing, although lack of thorough knowledge was found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentell et al (2015) found low health literacy, as measured by self-reported understanding of print health-related materials, was significantly related to cervical screening. Lack of knowledge can be an important determinant of cervical screening (Ayres et al, 2010); however, basic knowledge of cervical screening was found in two studies (Holroyd et al, 2003;Yoo et al, 2011). In Holroyd et al's (2003) quantitative study in Hong Kong with 98 Filipino domestic workers, despite 53% reported never having participated in pap-testing, 78% of women had heard of pap-testing, although lack of thorough knowledge was found.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive factors, such as knowledge and health beliefs, were discussed and linked to participation rates in nine studies (Maxwell et al, 2000;Holroyd et al, 2001;Fu et al, 2003;Holroyd et al, 2003;Kandula et al, 2006;Aitaoto et al, 2009;Ayres et al, 2010;Gor et al, 2011;Yoo et al, 2011). Sentell et al (2015) found low health literacy, as measured by a selfreported understanding of print health-related materials, was significantly related to cervical screening.…”
Section: Barriers and Facilitators To Cervical Screening: Cognitive Factorsmentioning
confidence: 99%
“…To provide evidence of construct validity, Mahon, Yarcheski, and Yarcheski (2002) factor analyzed the PLQ in a sample of 100 middle (aged 15-17) and 122 late (aged 18-21) adolescents, and also examined theoretically relevant variables in relation to PHPs. Relative to reliability, the following coefficient alphas were reported: (a) a .73 in 222 adolescents aged 15 to 21 (Mahon et al, 2002); (b) a .77 in a sample of 204 middle adolescents, aged 15 to17 (Ayres, 2008); (c) a .82 in a sample of 89 Filipino women, aged 18 to 21 (Ayres, Atkins, & Lee, 2010); and (d) a .72 in a sample of 163 college students aged 18 to 21 (Ayres & Mahat, 2012). A coefficient alpha of .72 was obtained in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Relative to reliability, the following coefficient alphas were reported: (a) a .91 in a sample of 204 middle adolescents, aged 15 to 17 (Ayres, 2008); (b) a .93 in a sample of Filipino women, aged 18 to 21 (Ayres et al, 2010); and (c) a .93 in 163 Asian American college students, aged 18 to 21 (Ayres & Mahat, 2012). The coefficient alpha in this study was .87.…”
Section: Methodsmentioning
confidence: 99%
“…Each language version obtained an overall Cronbach's alpha coefficient of .85, indicating high internal consistency among the items (dela Cruz et al., , ). Studies that have used this measure have shown appropriate coefficient alphas as evidence of its reliability and have been consistent with the theoretical literature (Ayers, Atkins, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%